2022
DOI: 10.1136/bmjopen-2021-057504
|View full text |Cite
|
Sign up to set email alerts
|

A pilot multicentre cluster randomised trial to compare the effect of trauma life support training programmes on patient and provider outcomes

Abstract: IntroductionTrauma accounts for nearly 10% of the global burden of disease. Several trauma life support programmes aim to improve trauma outcomes. There is no evidence from controlled trials to show the effect of these programmes on patient outcomes. We describe the protocol of a pilot study that aims to assess the feasibility of conducting a cluster randomised controlled trial comparing advanced trauma life support (ATLS) and primary trauma care (PTC) with standard care.Methods and analysisWe will pilot a pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It is well recognized that this is the key to reducing mortality in severely injured patients with unstable vital signs [ 40 ]. This approach has been popularized in North America by the American College of Surgeons at the end of the twentieth century and quickly spread all over the world [ 8 , 9 , 41 ]. Interestingly, in our SRs no primary study was found from European countries of either the ATLS or the ETC courses about the improvement in trauma care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well recognized that this is the key to reducing mortality in severely injured patients with unstable vital signs [ 40 ]. This approach has been popularized in North America by the American College of Surgeons at the end of the twentieth century and quickly spread all over the world [ 8 , 9 , 41 ]. Interestingly, in our SRs no primary study was found from European countries of either the ATLS or the ETC courses about the improvement in trauma care.…”
Section: Discussionmentioning
confidence: 99%
“…For trauma patients, several checklists based on a structured approach have been developed to improve the early management, such as the life support checklist explored in training programmes for trauma assessment and treatment [ 5 7 ]. The first training programmes were introduced by the American College of Surgeons with a worldwide spread in the past 20 years: Prehospital Trauma Care (PTC) and Advanced Trauma Life Support (ATLS ® ) [ 8 ]. Moreover, a branch of the ATLS programme was established also for nurses, the Advanced Trauma Course for Nurses (ATCN ® ) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We piloted a three-armed cluster randomised controlled trial. The protocol was published 8 . There were two intervention arms, ATLS ® and PTC training, and one standard care arm.…”
Section: Methodsmentioning
confidence: 99%
“…Trauma is a public health threat which claims an annual death toll of 4.5 million lives globally, contributing to 10% of global disease burden 1 . Over 90% of global deaths due to trauma disproportionately occur in low- and middle-income countries (LMICs) such as those in sub-Saharan Africa where trauma life support educational programs are scarce 1 . The main cause of trauma related deaths in Africa are road traffic crashes 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Several trauma care educational modules have been piloted in LMICs to address the unmet human resource needs but their impact assessment has been theoretical without the skills component 15 . Moreover, other than the ongoing clinical trial on the effect of advanced life support and primary trauma courses in India 1 , such trauma education programs have not been validated in randomized controlled settings, which could have affected their clinical application 16 .…”
Section: Introductionmentioning
confidence: 99%